2016
DOI: 10.1371/journal.pone.0168792
|View full text |Cite|
|
Sign up to set email alerts
|

The Intelligent Control System and Experiments for an Unmanned Wave Glider

Abstract: The control system designing of Unmanned Wave Glider (UWG) is challenging since the control system is weak maneuvering, large time-lag and large disturbance, which is difficult to establish accurate mathematical model. Meanwhile, to complete marine environment monitoring in long time scale and large spatial scale autonomously, UWG asks high requirements of intelligence and reliability. This paper focuses on the “Ocean Rambler” UWG. First, the intelligent control system architecture is designed based on the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Previously, in a survey from the Infectious Diseases Society of America, members of the Emerging Infections Network, 3 cases of active TB were reported in patients treated with RTX, but no further description of these patients is available [ 139 ]. Recently, a nationwide retrospective cohort study from Taiwan, a country at high TB risk, reported 2 cases of active TB in 763 patients with RA treated with RTX [ 140 ]. These 2 patients had a history of previous anti-TNF treatment, and active TB occurred after 8 and 10 years of RTX therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, in a survey from the Infectious Diseases Society of America, members of the Emerging Infections Network, 3 cases of active TB were reported in patients treated with RTX, but no further description of these patients is available [ 139 ]. Recently, a nationwide retrospective cohort study from Taiwan, a country at high TB risk, reported 2 cases of active TB in 763 patients with RA treated with RTX [ 140 ]. These 2 patients had a history of previous anti-TNF treatment, and active TB occurred after 8 and 10 years of RTX therapy.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 14b, given that the SPP method is optimized based on the initial path; it retains the fitness function standard of the initial planning and reduces the oscillation of the initial planning path through optimization. , and the trajectory tracking adopted the pure tracking (PP) method [35][36][37]. In the simulation experiment, when the time exceeded 50.0 s, the target point was replaced, although the vehicle had not reached the distance threshold of the target in the current tracking stage.…”
Section: J Mar Sci Eng 2019 7 X For Peer Reviewmentioning
confidence: 99%
“…On the Simulink simulation platform, a USV motion model was developed. The iterative step length and control cycle were 0.15 s. The parameters of the course PID controller were set as p = 1.0, i = 0.001, d = 1.0, the parameters of the speed controller were p = 2.0, i = 0.001, d = 0.001, and the trajectory tracking adopted the pure tracking (PP) method [35][36][37]. In the simulation experiment, when the time exceeded 50.0 s, the target point was replaced, although the vehicle had not reached the distance threshold of the target in the current tracking stage.…”
Section: J Mar Sci Eng 2019 7 X For Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical AIC methods include expert control, fuzzy control and neural network control. AIC methods have strong fault tolerance [10]. It can be used in nonlinear and complex control.…”
Section: Introductionmentioning
confidence: 99%